Educational Equity in a Globalized Era: Comparative Insights from Southeast Asia and Other Developing Regions - Widaningsih; Rahman, Najib Aulia (Yayasan Sinergi Kawula Muda, 2023)
Globalization continues to reshape education systems worldwide, compelling national governments to reassess and reform their educational policies. This study explores how globalization affects national education policy across social, economic, and governance dimensions. Using a systematic narrative review methodology, literature was collected from Scopus, PubMed, and Google Scholar using targeted keywords such as